Electro-generation of hydrogen peroxide using a graphite cathode from exhausted batteries: study of influential parameters on electro-Fenton process. Issue 11 (11th May 2020) - Diouf, Ibrahima; Dia, Oumar; Diedhiou, Moussa Bagha; Drogui, Patrick; Toure, Alpha Ousmane; Lo, Sidy Mambaye; Rumeau, Michel; Mar/Diop, Codou Gueye
ABSTRACT: In this work, the study of hydrogen peroxide (H2 O2 ) electro-generation using graphite from exhausted batteries (Gr-Bat) was conducted. Linear sweep voltammetry and electrolysis experiments were carried out in a single compartment electrochemical cell. Study of the possibility to use this electrode revealed that it presents, as vitreous carbon (VC) electrode, a reduction of oxygen with two successive waves (bi-electronic reduction). The first wave corresponds to the reduction of O2 to H2 O2, while the second one corresponds to the reduction of H2 O2 to H2 O. The cathodic potentials for electro-generation of H2 O2 appeared at −600 and –700 mV vs. Ag/AgCl for Gr-Bat and VC electrodes, respectively. Subsequently, electrolysis experiments were conducted by imposing the potentials required for H2 O2 formation. The effect of several operating parameters on H2 O2 production, such as the nature and concentration of the electrolyte, the pH, the presence of ferrous ions and O2 injection were studied using Gr-Bat and VC electrodes, respectively. For both electrodes, the acidic medium was more favorable for H2 O2 electro-generation. The oxygen injection in solution promoted an increase of H2 O2 concentration, but its effect was more pronounced in the case of VC electrode. Application for crystal violet degradation by electro-Fenton revealed that Gr-Bat had the best purification performance. A removal rate of 73.18% was obtained with Gr-Bat electrode against 62.27% with VC electrode for an electrolysis time of 120 min. This study has demonstrated the possibility of recycling Gr-Bat by using them as cathode materials in the electro-Fenton process. GRAPHICAL ABSTRACT: